Ultrasound- assisted extraction propolis and its kinetic study - Najihah, Yusof; Mimi Sakinah, A. M.; Veloo, Kutty R. (IOP Publishing, 2020)
In current times, there has been a growing attention in the consumption of functional food such as propolis due to the abundant of available bioactive compounds such as polyphenols. There are several health properties of propolis reported on having a huge spectrum of biological properties including anti- inflammatory, antioxidant, anticancer and antimicrobial. Maceration is known for its longer extraction time issue. Ultrasonic- assisted extraction is seen as an alternative to solve this problem. This study focused on indicating the factors influencing solid liquid ultrasonic- assisted extraction of total polyphenols content (TPC) from propolis using ethanol as solvent. The effects of three main factors; temperature (25°C, 35°C, 45°C, 55°C, 65°C), reaction time (5, 10, 15, 20, 25 minutes) and concentration of ethanol (50:50, 60:40, 70:30, 80:20, 90:10) (v/v) were studied to achieve maximum total phenolic content. The optimum conditions for ultrasonic- assisted extraction of phenolic content from propolis are with 70% ethanol, at 65°C for 25 mins. From the experimental data of kinetics study, the ultrasonic extraction of phenolic compounds from propolis is the second- order kinetic model and the extraction constant (k2) was 2.8998 g mg-1 min-1 .